2016
DOI: 10.1002/2015ja021545
|View full text |Cite
|
Sign up to set email alerts
|

Statistical correlation of low‐altitude ENA emissions with geomagnetic activity from IMAGE/MENA observations

Abstract: Plasma sheet particles transported Earthward during times of active magnetospheric convection can interact with exospheric/thermospheric neutrals through charge exchange. The resulting Energetic Neutral Atoms (ENAs) are free to leave the influence of the magnetosphere and can be remotely detected. ENAs associated with low‐altitude (300–800 km) ion precipitation in the high‐latitude atmosphere/ionosphere are termed low‐altitude emissions (LAEs). Remotely observed LAEs are highly nonisotropic in velocity space s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Therefore, parent particles regularly undergo multiple charge exchanges and stripping collisions to create ENA emissions (Bazell et al, 2010;Roelof, 1997). LAEs are bright and perpendicular to the local magnetic field due to the gyro-tropic behavior of parent ions (Mackler et al, 2016;Pollock et al, 2009). Brandt et al (1997) analyzed 26-to 52-keV ENA images from Prelude in Planetary Particle Imaging, on the Swedish satellite Astrid (Barabash et al, 1997), and found that LAE flux enhancements occur during the main phase of geomagnetic storms.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, parent particles regularly undergo multiple charge exchanges and stripping collisions to create ENA emissions (Bazell et al, 2010;Roelof, 1997). LAEs are bright and perpendicular to the local magnetic field due to the gyro-tropic behavior of parent ions (Mackler et al, 2016;Pollock et al, 2009). Brandt et al (1997) analyzed 26-to 52-keV ENA images from Prelude in Planetary Particle Imaging, on the Swedish satellite Astrid (Barabash et al, 1997), and found that LAE flux enhancements occur during the main phase of geomagnetic storms.…”
Section: Introductionmentioning
confidence: 99%
“…Brandt et al (1997) analyzed 26-to 52-keV ENA images from Prelude in Planetary Particle Imaging, on the Swedish satellite Astrid (Barabash et al, 1997), and found that LAE flux enhancements occur during the main phase of geomagnetic storms. Mackler et al (2016) performed a statistical investigation using the Medium Energy Neutral Atom instrument on the IMAGE satellite (Pollock et al, 2000) and reported a generally positive correlation between LAE intensities and geomagnetic indices, such as the longitudinally symmetric disturbance index (Sym-H, a higher-cadence representative of the Dst index), the auroral electrojet index (AE), and the Kp index. They found that the LAE intensity had the strongest correlation with Sym-H, though the temporal profiles were not studied.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations